Population of Cattle Egret (Bubulcus Ibis) at the Grassland of University Putra Malaysia, Serdang Selangor, Malaysia - Maling, Sat (1999)
A study of population of the Cattle Egret (Bubulcus ibis) was conducted at the Grassland, University Putra Malaysia, Serdang Selangor. The objectives of this study were to (1) estimate the population size and (2) examine the feeding habitats of egrets. Distance Sampling Method was used for this study where five transects namely Transect A, Transect B, Transect C, Transect D and Transect E were established randomly in the study area. The length of each transect A, B, C, D and E was 390 m, 370 m, 310 m, 500 m and 480 m respectively. Each line was surveyed continuously at 3 days with two in morning and afternoon. Program DISTANCE V2.2 was used to estimate the density. Feeding habitat of Cattle Egret was conducted by direct observation. The density of Cattle Egret ranged from 2.51 to 4.34 individuals per hectare. The population size of egrets at the Grassland area of University Putra Malaysia, Serdang Selangor, Malaysia ranged from 648 to 1120 birds. The feeding habitat of egret was found to be associated with cattle. However, the number of egrets was less when the cattles were not feeding in the field, because cattles provided flies and cattle ticks for egrets.